Evaluation of Iso-Butyric acid and Acetic acid in Landfill Leachate Emissions-Mid Auchencarroch Experimental Design - C. KOLIOPOULOS, TELEMACHUS; GEORGIA KOLIOPOULOU, M.D. (Asian Journal of Chemistry, 2010)
The biodegradation of Mid Auchencarroch experimental landfill project is studied in four different cells. This paper analyses the effects of waste pretreatment and different waste management techniques on characteristic organic acids emissions and biomass biodegradation stages. The variations of the examining experimental landfill emissions are presented and analyzed. The experimental Mid Auchencarroch's data confirm that waste pretreatment, co-disposal with inert material and leachate recirculation are sustainable and accelerate the waste biodegradation, protecting public health from associated landfill emissions' risks.